Violations of the content of the transaction as one of the grounds for invalidity of the transaction (Journal of actual problems of jurisprudence, 2019)
This paper focuses on the grounds of invalidity of transactions under the laws of the Republic of Kazakhstan, in particular, this paper focuses on the problems of violations of requirements for the content of the transaction as one of the grounds for invalidity of the transaction.